Neutralization of CXCL12 attenuates established pulmonary hypertension in rats. Issue 3 (7th June 2019) - Bordenave, Jennifer; Thuillet, Raphaël; Tu, Ly; Phan, Carole; Cumont, Amélie; Marsol, Claire; Huertas, Alice; Savale, Laurent; Hibert, Marcel; Galzi, Jean-Luc; Bonnet, Dominique; Humbert, Marc; et al.
Abstract: Aims : The progressive accumulation of cells in pulmonary vascular walls is a key pathological feature of pulmonary arterial hypertension (PAH) that results in narrowing of the vessel lumen, but treatments targeting this mechanism are lacking. The C-X-C motif chemokine 12 (CXCL12) appears to be crucial in these processes. We investigated the activity of two CXCL12 neutraligands on experimental pulmonary hypertension (PH), using two complementary animal models. Methods and results : Male Wistar rats were injected with monocrotaline (MCT) or were subjected to SU5416 followed by 3-week hypoxia to induce severe PH. After PH establishment, assessed by pulsed-wave Doppler echocardiography, MCT-injected or SU5416 plus chronic hypoxia (SuHx) rats were randomized to receive CXCL12 neutraligands chalcone 4 or LIT-927 (100 mg/kg/day), the C-X-C motif chemokine receptor 4 (CXCR4) antagonist AMD3100 (5 mg/kg/day), or vehicle, for 2 or 3 weeks, respectively. At the end of these treatment periods, echocardiographic and haemodynamic measurements were performed and tissue samples were collected for protein expression and histological analysis. Daily treatment of MCT-injected or SuHx rats with established PH with chalcone 4 or LIT-927 partially reversed established PH, reducing total pulmonary vascular resistance, and remodelling of pulmonary arterioles. Consistent with these observations, we found that neutralization of CXCL12 attenuates right ventricular hypertrophy, pulmonary vascular remodelling, and decreases pulmonary artery smooth muscle cell (PA-SMC) proliferation in lungs of MCT-injected rats and SuHx rats. Importantly, CXCL12 neutralization with either chalcone 4 or LIT-927 inhibited the migration of PA-SMCs and pericytes in vitro with a better efficacy than AMD3100. Finally, we found that CXCL12 neutralization decreases vascular pericyte coverage and macrophage infiltration in lungs of both MCT-injected and SuHx rats. Conclusion : We report here a greater beneficial effect of CXCL12 neutralization vs. the conventional CXCR4 blockade with AMD3100 in the MCT and SuHx rat models of severe PH, supporting a role for CXCL12 in the progression of vascular complications in PH and opening to new therapeutic options. Graphical Abstract: